2010
DOI: 10.1111/j.1365-2621.2010.02451.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality, sensory quality and consumer acceptability of sorghum and bread wheat biscuits fortified with defatted soy flour

Abstract: SummaryBiscuits were produced by compositing sorghum or bread wheat flours with defatted soy flour.Compared to the 100% cereal biscuits, sorghum-soy and bread wheat-soy 1:1 ratio composite biscuits had at least double the protein content and the lysine content increased by 500-700%.For the sorghum-soy biscuits, in vitro protein digestibility increased by 170%. Two such biscuits of 28 g each could provide 50% of the recommended daily protein intake for 3 to 10 year olds.Descriptive sensory evaluation revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 33 publications
15
96
0
Order By: Relevance
“…1(b) shows that with the increase in the level of sorghum and inulin, the fracturability of biscuits decreases. (Serrem et al 2011) reported that sorghum biscuits were associated with dry and crispy texture. Crispiness in sorghum biscuits could be probably because of the absence of gluten.…”
Section: Resultsmentioning
confidence: 99%
“…1(b) shows that with the increase in the level of sorghum and inulin, the fracturability of biscuits decreases. (Serrem et al 2011) reported that sorghum biscuits were associated with dry and crispy texture. Crispiness in sorghum biscuits could be probably because of the absence of gluten.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean is one of the most important oil and protein crops of the world containing 30 to 45% protein with a good source of all indispensable amino acids (Islam et al, 2007;Serrem et al, 2011). Recently, soybean is extensively and effortlessly grown for making diverse processed foods (Otunola et al, 2006) and worldwide production was recorded as 217.60 MT in 2005-07 and predicted to increase 2.20% or 371.3MT by 2030 (Tadayoshi and Peter, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the meal obtained after oil extraction also possess a rich amount of protein which could be utilized for value addition of various food products. On the other hand most of the developing countries are facing a problem of various forms of protein energy malnutrition [2]. Hence peanuts as a cheap source of protein has aroused recently in traditional foods as well as other foods such as peanut butter etc.…”
Section: Introductionmentioning
confidence: 99%